2013
DOI: 10.1021/ci3005308
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of QSAR Models on the Selection of Trial Descriptor Sets: A Demonstration Using Nanotoxicity Endpoints of Decorated Nanotubes

Abstract: Little attention has been given to the selection of trial descriptor sets when designing a QSAR analysis even though a great number of descriptor classes, and often a greater number of descriptors within a given class, are now available. This paper reports an effort to explore interrelationships between QSAR models and descriptor sets. Zhou and co-workers (Zhou et al., Nano Lett. 2008, 8 (3), 859-865) designed, synthesized, and tested a combinatorial library of 80 surface modified, that is decorated, multi-wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 36 publications
(60 reference statements)
0
49
1
Order By: Relevance
“…We previously explored (Shao et al, 2013) the relationship between the six nanotoxicity endpoints and different molecular descriptor classes (Tseng et al, 2012) to develop optimum QSAR models for each of the six endpoint training sets as reported by Zhou et al (Zhou et al, 2008). The resulting high quality and optimal QSAR models based on molecular information, capturing the individual decorator and the complete DNC, indicated that each of the endpoints required a different combination of descriptor classes.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously explored (Shao et al, 2013) the relationship between the six nanotoxicity endpoints and different molecular descriptor classes (Tseng et al, 2012) to develop optimum QSAR models for each of the six endpoint training sets as reported by Zhou et al (Zhou et al, 2008). The resulting high quality and optimal QSAR models based on molecular information, capturing the individual decorator and the complete DNC, indicated that each of the endpoints required a different combination of descriptor classes.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The first is that the proposed mechanical mechanisms have been derived from optimized QSAR models (Shao et al, 2013) as "mechanism of action" templates. Instead of examining specific descriptors -physicochemical properties -in isolation, all of the molecular properties within the QSAR model are viewed as a whole.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, there is a growing literature on the use of (Q)SARlike models in nanotoxicology studies. There are a great number of reviews [3,5,10,[12][13][14] and research articles [15][16][17][18][19][20][21][22][23][24][25][26][27][28] devoted to the investigations of in silico modelling of ENM toxicity in peer-reviewed scientific journals.…”
Section: "[Insert Figure 1 About Here]"mentioning
confidence: 99%
“…Having an agreement on suitable descriptors is important, as past workers found that the choice of descriptors can affect the quality, significance and interpretation of nano-(Q)SAR model 10,52 . It may be that descriptors can be selected or adapted from traditional chemical descriptors, but it is highly likely that descriptors specifically developed for nanomaterials are needed.…”
Section: Barrier 1: the Generation Of A Reliable Modelmentioning
confidence: 99%